Validated High-Performance Liquid Chromatographic Method for the Estimation of Rosuvastatin Calcium in Bulk and Pharmaceutical Formulations - Ashour, Safwan (Master Publishing Group, 2011)
A reversed-phase high-performance liquid chromatographic method was developed and validated for the determination of rosuvastatin calcium in pharmaceutical dosage forms. The determination was performed on a Nucleodur column C(8) (250 × 4.6 mm i.d., 5 μm particle size); the mobile phase consisted of a mixture of 0.1M formic acid and methanol (25:75, v/v), pumped at a flow rate 1.0 mL min(-1). The photodiode array detector was operated at 280 nm. The retention times for rosuvastatin and fluvastatin, which was used as internal standard, were 3.98 and 7.78 min, respectively. Linearity range (r(2) better than 0.999, n=6) was 3.0-1602.0 μg mL(-1) with limit of detection value of 0.12 μg mL(-1). The precision of the method was demonstrated using intra- and inter-day assay RSD% values which were less than 2.40%, while the recovery was 99.86-102.86%. The method was applied in the quality control of commercial tablets and content uniformity test and proved to be suitable for rapid and reliable quality control.